The Used of Cooperative Learning And Peer Feedback To Improve Students Speaking Skill at Vocational Hight School Qamarul Huda - Yatna, Mazhuri Bakti; Syukron Siddik, Ahmad; Hasbullah , Hasbullah (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study investigates the effectiveness of Cooperative Learning strategies combined with Peer Feedback in improving the English-speaking skills of tenth-grade students at SMK Qamarul Huda during the academic year 2025/2026. Employing a quantitative approach with a one-group pre-test and post-test design, the research involved 21 students as participants. Data were collected using speaking performance assessments focusing on fluency, pronunciation, grammar, vocabulary, and comprehension. Statistical analyses were conducted using paired sample t-tests with SPSS version 29. Results revealed a significant improvement in students’ speaking performance after the implementation of Cooperative Learning and Peer Feedback, with the mean score rising from 62.7 (pre-test) to 72.2 (post-test). The paired sample t-test indicated a Sig. (2-tailed) value of 0.000 < 0.05, confirming a statistically significant difference. Findings demonstrate that Cooperative Learning fosters interaction and participation, while Peer Feedback provides constructive reflection and correction, thus enhancing confidence and linguistic accuracy. The study concludes that integrating these two approaches is effective in fostering meaningful and interactive speaking practice for vocational school students.